STUDY OF THE FORMULATION OF JICAMA FLOUR (Pachyrhizus erosus) AND WHEAT FLOUR IN MANUFACTURING BROWNIES CHIPS - Salsabila, Az Zahra Fithri; -, Suharyono; Herdiana, Novita (Jurnal Agroindustri Berkelanjutan, 2025)
Brownies chips are a snack made from brownies dough that is molded into thin squares and baked dry to produce brownies chips that are easy to consume and last a long time. The aim of this research is to determine the formulation of jicama flour (Pachyrhizus erosus) and wheat flour which produces brownies chips with the best sensory properties. This research was structured in a Complete Randomized Block Design (RAKL) with six treatments and four replications. The formulation treatment of jicama flour and wheat flour consisted of 6 levels, namely T0 (0% : 100%), T1 (10% : 90%), T2 (20% : 80%), T3 (30% : 70%), T4 (40% : 60%), T5 (50% : 50%). Data were analyzed using the Bartlett test and Tuckey test, followed by analysis of variance (ANARA), and the Least Significant Difference (BNT) test at the 5% level. Based on the research results, brownies chips with a formulation of jicama flour and wheat flour that produces the best sensory results is the T4 treatment (40% jicama flour : 60% wheat flour) which has a sweet and distinctive chocolate taste, blackish brown color, crunchy and dense texture, and aromatic. typical brownies chips. The results of the chemical analysis of the brownies chips were water content 3,76%, ash content 2,34%, protein content 13,87%, fat content 25,61%, carbohydrate content 54,42%, and crude fiber content 6,01%. The calculation results for the calorific value of brownies chips per 100 grams are 503,65 kcal.